Evaluasi Penggunaan Antibiotik Pada Kasus Demam Tifoid Pasien Pediatrik Di Instalasi Rawat Inap Rsu Harapan Ibu Purbalingga Tahun 2022 - Dyah Ayu Widowati; Adha Anugrah Ibrahim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Typhoid fever is a systemic infection that occurs especially in children due to the compromised state of the immune system and organs are still developing and not perfect. Typhoid fever ranks 4th out of the top 20 pediatric sub-specialty diseases in 2022 and the use of antibiotics that exceed the dose (overdose) at Harapan Ibu Purbalinga Hospital. This research aims to assess the appropriateness of antibiotic treatment in young patients and to review the use of antibiotics in typhoid fever, focusing on accurate diagnosis, appropriate patient selection, appropriate antibiotic selection, correct dosing schedule and optimal duration of treatment (5T). The approach used in this research was the qualitative descriptive technique. The data collection process involved obtaining historical data (medical records) from 100 paediatric inpatients at Harapan Ibu Purbalingga Hospital. The results of this study showed that the gender classification of male patients totaled 55 patients while female patients totaled 45 patients. The age range classification of 1-5 years has the highest number with a percentage of 41%. Antibiotics that are often used are cephalosforin group (72%) while for other classes of antibiotics used for pediatric typhoid fever are penicillin group (28%). When examining the appropriateness of drug use, the results showed that the accuracy of correct diagnoses was 100%, the accuracy of matching patients was 100%, the accuracy of selecting the appropriate antibiotic was 100%, the accuracy of determining dosage was 84%, and the accuracy of determining the correct duration of treatment was 100%.